Glycaemic control and familial factors determine hyperlipidaemia in early childhood diabetes. Oxford Regional Prospective Study of Childhood Diabetes. - Abraha, A; Schultz, C; Konopelska-Bahu, T; James, T; Watts, A; Stratton, I; Matthews, DR; Dunger, D (1999)
AIMS: To determine whether abnormal lipid levels in children with Type 1 diabetes mellitus are the result of poor metabolic control or may in part be determined by genetic factors. METHODS: Non-fasting lipid levels were measured in 141 children with Type 1 diabetes (age range 7.7-19 years) 3 years after diagnosis, and in 192 of their parents. Glycosylated haemoglobin and the urinary albumin-creatinine ratio (three urine samples) were estimated in each child annually. RESULTS: The children had a mean total cholesterol of 4.46 +/- 1.25 mmol/l (+/- SD) and a median triacylglycerol of 1.18 mmol/l (range 0.32-4.7). A total of 15.3% of the population had a total cholesterol > 5.2 mmol/l and 17.9% had a triacylglycerol > 1.7 mmol/l; in 5.6% both total cholesterol and triacylglycerol were greater than these cut-off points. Total cholesterol, triacylglycerol and very low density lipoprotein-cholesterol were significantly correlated to glycaemic control. However, total cholesterol was also significantly related to parental total cholesterol either as analysed separately or as mean parental total cholesterol (r = 0.37, P = 0.0001). In stepwise multiple regression analysis both mean parental total cholesterol (P = 0.001) and HbA1c (P = 0.015) were significant determinants of the child's total cholesterol. The children studied were being followed prospectively for the development of microalbuminuria and there was a weak association across tertiles of total cholesterol, linking higher levels to the development of microalbuminuria (P < 0.05). CONCLUSIONS: We conclude that both glycaemic control and familial factors may be important determinants of lipid levels in young people with diabetes. Both may contribute to the subsequent risk of cardiovascular disease and possibly the development of incipient diabetic nephropathy.